Collusion Facilitating and Collusion Breaking Power of Simultaneous Ascending and Descending Price Auctions. - Brown, Alexander L.; Plott, Charles R.; Sullivan, Heidi J. (Economic Inquiry, 2009)
This article demonstrates that a robust tacit collusion evolves quickly in a “collusion incubator” environment but is destroyed by the simultaneous descending price auction. Theories of collusion-producing behavior, along with the detail of the states on which strategies are conditioned, lead to a deeper understanding of how tacit collusion evolves and its necessary conditions. These theories explain how the descending price auction destroys the collusion. The experiments proceed by conducting simultaneous ascending price auctions in the collusion incubator. Then, once the tacit collusion developed, changing to the descending auction. The change moved prices from collusive levels to near-competitive levels. (JEL C71, C92, D43, D44) Reprinted by permission of the publisher.